Transfer of 99mTc DTPA and bronchoalveolar lavage findings in patients with asymptomatic extrinsic allergic alveolitis. - Schmekel, B (1990)
An investigation was performed to determine whether symptom free patients with previously diagnosed extrinsic allergic alveolitis had signs of inflammation in the lung. Pulmonary clearance of inhaled technetium-99m labelled diethylene triamine penta-acetic acid (DTPA) was measured in seven patients with a history of extrinsic allergic alveolitis but with no symptoms at the time of the study and in 12 control subjects. Monoexponential clearance curves were obtained in all 12 control subjects. In contrast, lung clearance was abnormal in five of the seven patients: biexponential clearance curves were noted in four and an abnormally rapid monoexponential curve in one. Bronchoalveolar lavage was performed in all patients. Fluid from the second and third aliquots showed increased concentrations of albumin and urea in fluids from the patients, suggesting increased plasma leakage through the alveolocapillary membranes. More eosinophils and more eosinophil cationic protein were also found in the lavage fluid from the patients. The trend towards increased numbers of eosinophils in patients with abnormal lung clearance of DTPA suggests that this may be due to a continuing inflammatory reaction. Lung inflammation was also suggested by the fact that less leukotriene B4 was secreted by cultured alveolar macrophages obtained from patients than by control macrophages. It is concluded that symptom free patients with previous extrinsic allergic alveolitis have continuing alveolar disease as shown by lung clearance and lavage findings.